2015
DOI: 10.1108/mrr-12-2013-0293
|View full text |Cite
|
Sign up to set email alerts
|

Influence of institutional profiles on time to recall

Abstract: Purpose – This paper aims to understand why firms expedite or delay product recall decisions involving international sourcing. Design/methodology/approach – This paper combines US toy recall data from the Consumer Products Safety Commission database for the period from 1988to 2011 with World Economic Forum data on institutional environments to predict the effect the host country conditions have on recall timing decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Then, following Baum and Ingram, 1998;Haunschild and Sullivan, 2002) ------Please insert table 4 about here------Second, we controlled for country of manufacturing as majority of the toys sold in the US are imported from developing economies (Bapuji, 2011). While country of origin has been shown to influence consumer attributions of blame in product recall situations (Carvalho et al, 2015), extant research specifically suggests that import country of origin influences recall timing decisions (Majid and Bapuji, 2018;Muralidharan et al, 2015). Muralidharan et al (2015) characterized institutional unfavorability of the import country and predicted timing decisions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, following Baum and Ingram, 1998;Haunschild and Sullivan, 2002) ------Please insert table 4 about here------Second, we controlled for country of manufacturing as majority of the toys sold in the US are imported from developing economies (Bapuji, 2011). While country of origin has been shown to influence consumer attributions of blame in product recall situations (Carvalho et al, 2015), extant research specifically suggests that import country of origin influences recall timing decisions (Majid and Bapuji, 2018;Muralidharan et al, 2015). Muralidharan et al (2015) characterized institutional unfavorability of the import country and predicted timing decisions.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the more unfavourable the import country's institutions are, quicker are the defective products recalled from the market. We followed the same methodology followed by Muralidharan et al (2015) to create institutional unfavorability and used it as a control. The sample set reduced to 707 recalls as some of the recall notices did not indicate country of import.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corporate social responsibility (hence CSR) practice, defined as voluntary policies, practices, and programs that go beyond narrow economic and legal requirements, have drawn worldwide attention in recent years [1][2][3][4]. Businesses today are well aware that they are expected to simultaneously address economic, environmental, and ethical-social concerns, that is, contribute to the triple bottom lines [5].…”
Section: Introductionmentioning
confidence: 99%